Pengaruh Penerapan Akuntansi Publik Dan Kualitas Peraturan Perundangan Terhadap Kualitas Laporan Keuangan Dan Akuntabilitas Kinerja Instansi Pemerintah - Pamungkas, Bambang (Jurnal Ilmiah Ranggagading (JIR), 2012)
This research analyzes the effect of the implementation of public accounting, the quality of legislation on the quality of financial reports and their implications for government performance accountability system level local governments of Yogyakarta provinces privileges . Methods of data analysis using path analysis. The results showed that: 1) Implementation of public sector financial accounting and quality regulations affect the quality of government financial statements either partially or simultaneously. 2) Implementation of public sector financial accounting, quality regulations and the quality of financial reports of government influence on government performance accountability either partially or simultaneously.